Technology Implementation in Elderly Care: Subject Positioning in Times of Transformation. (October 2019) - Segercrantz, Beata; Forss, Maria
Innovation is often celebrated as a solution to various challenges in care work. Thus, a growing number of care workers are likely to experience innovations in their daily work. This article examines how care workers and project workers in elderly care are affected by contemporary transformations by exploring: (1) how they construct meanings around innovation implementation and (2) are subject positioned in relation to these meanings. Drawing on discourse analysis, we conduct a case study and analyze semistructured interviews, observations, and organizational documents. We illustrate how innovation is constructed in terms of optimism, and also as a source for struggle, with specific effects on care workers' subject positioning. The findings thus contribute to new insights into the contemporary dominating discourse of innovation and its implications at the level of practice and subjectivity.